A phase II study of anlotinib combined with etoposide and platinum‐based regimens in the first‐line treatment of extensive‐stage small cell lung cancer. Issue 10 (7th April 2022) - Liu, Chang; Liao, Jiatao; Wu, Xianghua; Zhao, Xinmin; Sun, Si; Wang, Huijie; Hu, Zhihuang; Zhang, Yao; Yu, Hui; Wang, Jialei
Abstract: Background: The aim of this prospective, pilot, single‐arm phase II trial was to evaluate the safety and efficacy of anlotinib combined with etoposide and platinum‐based regimens in the first‐line treatment of extensive‐stage small cell lung cancer (ES‐SCLC). Methods: This phase II study was conducted at Fudan University Shanghai Cancer Center between December 2018 and December 2020. All patients received standard chemotherapy (etoposide plus cisplatin/carboplatin) consisting of four courses and anlotinib at 12 mg once per day for 2 weeks followed by a one‐week rest. Anlotinib administration was continued until disease progression, intolerable adverse events (AEs) or patient withdrawal from the study. The primary outcome measure was progression‐free survival (PFS). The secondary outcome measures were overall survival (OS), objective control rate (ORR), disease control rate (DCR) and AEs. Results: Thirty‐seven patients were included in this study, and 30 patients were eligible for efficacy analysis. ORR and DCR were 90.0% and 96.7%, respectively. The estimated PFS and OS were 6.0 months (95% CI: 1.1–11.9 months) and 14.0 months (95% CI: 8.6–19.4 months), respectively. No unexpected adverse effects were reported. Hypertension (20/37, 54.1%), anemia (16/37, 43.2%), alopecia (15/37, 40.5%), elevated transaminases (9/37, 24.3%) and alkaline phosphatase (9/37, 24.3%) were the most commonly reported AEs. Thirteen patients (35.1%) reported grade 3–5 AEs. No treatment‐related deaths occurred during this study. Conclusion: The addition of anlotinib to standard etoposide/platinum chemotherapy achieved encouraging PFS and OS in previously untreated ES‐SCLC patients, with an acceptable tolerability profile and no new safety signals observed. Abstract : Anlotinib (AL3818), an oral, small‐molecular tyrosine kinase inhibitor, was approved as a first third‐ and further‐line treatment regime of relapsed SCLC in China in 2019. This study showed that the addition of anlotinib to standard etoposide/platinum chemotherapy achieved encouraging PFS and OS in previously untreated extensive‐stage small cell lung cancer (ES‐SCLC) patients, with an acceptable tolerability profile and no new safety signals observed.